2018
DOI: 10.1007/s12264-018-0279-6
|View full text |Cite
|
Sign up to set email alerts
|

A Context-Based Analgesia Model in Rats: Involvement of Prefrontal Cortex

Abstract: Cognition and pain share common neural substrates and interact reciprocally: chronic pain compromises cognitive performance, whereas cognitive processes modulate pain perception. In the present study, we established a non-drug-dependent rat model of context-based analgesia, where two different contexts (dark and bright) were matched with a high (52°C) or low (48°C) temperature in the hot-plate test during training. Before and after training, we set the temperature to the high level in both contexts. Rats showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Since the dorsomedial (prelimbic) prefrontal cortex has been implicated in some forms of adaptive behavior [14,35], as well as the processing of pain [44,45] before, we investigated the effects of mPFC inactivation on responding. We found that mPFC inactivation resulted in a slight decrease of responding even before the onset of punishment and prevented the shift of choice allocation away from the punished port, relative to saline controls.…”
Section: Discussionmentioning
confidence: 99%
“…Since the dorsomedial (prelimbic) prefrontal cortex has been implicated in some forms of adaptive behavior [14,35], as well as the processing of pain [44,45] before, we investigated the effects of mPFC inactivation on responding. We found that mPFC inactivation resulted in a slight decrease of responding even before the onset of punishment and prevented the shift of choice allocation away from the punished port, relative to saline controls.…”
Section: Discussionmentioning
confidence: 99%
“…To do this, hotplates set to different temperatures, one less noxious and one more noxious, are paired with distinct contextual cues. After conditioning to the less noxious hotplate-context pairing, rodents were found to exhibit decreased nocifensive behavior on test day when the temperature was raised to a more noxious temperature in the same context Xu et al, 2018). Critically, these studies revealed that pain expectancy-based placebo analgesia involved endogenous opioid signaling, as naloxone treatment blocked the expression of placebo analgesia on test day.…”
Section: Box 3 Limitations Of Rodent Models Of Placebo Analgesiamentioning
confidence: 98%
“…This information allows for the top-down modulation of pain via expectation and placebo processes (Coulombe et al, 2016;Huang et al, 2019). Indeed, placebo-induced analgesia occurs alongside decreased ACC activation, and pharmacological blockade of opioid receptors or the modulation of pyramidal neuron activity in the PFC prevents placebo analgesia Xu et al, 2018). In Section 5, we detail the role of opioid signaling in predictive coding and placebo circuits.…”
Section: Box 2 Improving the Study Of Negative Valence Directed Atten...mentioning
confidence: 99%
“…Although a number of studies have reported nonanalgesic placebo effects in animals in the past few decades [20,21], there have been few reports on analgesic responses in mice or rats, and almost all existing animal models employ Pavlovian conditioning paradigms and measure behavioral pain responses in naı ¨ve animals [22][23][24][25][26][27]. However, studies using physiological pain do not resemble the real clinical situation.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%